Outcomes of Two Different Techniques Using the Lateral Approach for Lumbar Interbody Arthrodesis. (August 2015) - Cheng, Ivan; Briseño, Michael R.; Arrigo, Robert T.; Bains, Navpreet; Ravi, Shashank; Tran, Andrew
Study Design: Retrospective cohort study. Objective: To determine the short-term outcomes of two different lateral approaches to the lumbar spine. Methods: This was a retrospective review performed with four fellowship-trained spine surgeons from a single institution. Two different approach techniques were identified. (1) Traditional transpsoas (TP) approach: dissection was performed through the psoas performed using neuromonitored sequential dilation. (2) Direct visualization (DV) approach: retractors are placed superficial to the psoas followed by directly visualized dissection through psoas. Outcome measures included radiographic fusion and adverse event (AE) rate. Results: In all, 120 patients were identified, 79 women and 41 men. Average age was 64.2 years (22 to 86). When looking at all medical and surgical AEs, 31 patients (25.8%) had one or more AEs; 22 patients (18.3%) had a total of 24 neurologically related AEs; 15 patients (12.5%) had anterior/lateral thigh dysesthesias; 6 patients (5.0%) had radiculopathic pain; and 3 patients (2.5%) had postoperative weakness. Specifically, for neurologic AEs, the DV group had a rate of 28.0% and the TP group had a rate of 14.2% ( p  < 0.18). When looking at the rate of neurologic AEs in patients undergoing single-level fusions only, the DV group rate was 28.6% versus 10.2% for the TP group ( p  < 0.03). Conclusion: Overall, 18.3% of patients sustained a postoperative neurologic AE following lateral interbody fusions. The TP approach had a statistically lower rate of neurologic-specific AE for single-level fusions.